STUDY ON THE STABILITY OF TRIVALENT CATIONS GADOLINIUM (Gd) DOPED FERRIC OXIDE (Fe2O3) THROUGH ATOMISTIC MODELING - Anggi Suprabawati (Akta Kimia Indonesia, 2020)
This research is aimed to study the stability of the structure Fe2O3 doped with trivalent cations Gadolinium (Gd) into compound Fe1-xGdxO2-δ through atomistic modeling and Bond Valence Sum (BVS) calculations. Short range potential used in this study was Buckingham potential. Result of geometry optimization at constant pressure shown the more of the concentration and the size of substituting dopant of ferric oxide (Fe2O3)increase, the more positive the lattice energy of the doped structure is, so that the stability of the doped Fe2O3 structure decreases.